Treatment of Rituximab-induced Crohn's Disease With Ustekinumab Induction and Long-term Maintenance of Remission. Issue 1 (6th November 2019) - Shankar, Uday; Vijayasekar, Kavitha; Bansal, Raghav; Walfish, Aaron
Abstract : Rituximab-induced Crohn's disease is a rare entity with very little literature on its management. We report the first case of this condition treated successfully with ustekinumab induction and long-term maintenance of remission.